Use of Rituximab in Childhood Idiopathic Nephrotic Syndrome. Issue 4 (22nd April 2023) - Chan, Eugene Yu-hin; Yap, Desmond Yat-hin; Colucci, Manuela; Ma, Alison Lap-tak; Parekh, Rulan S.; Tullus, Kjell
Abstract : Rituximab is an established therapy in children with idiopathic nephrotic syndrome to sustain short- to medium-term disease remission and avoid steroid toxicities. Recent trials focus on its use as a first-line agent among those with milder disease severity. Rituximab is used in multidrug refractory nephrotic syndrome and post-transplant disease recurrence, although the evidence is much less substantial. Available data suggest that the treatment response to rituximab depends on various patient factors, dosing regimen, and the concomitant use of maintenance immunosuppression. After repeated treatments, patients are found to have an improving response overall with a longer relapse-free period. The drug effect, however, is not permanent, and 80% of patients eventually relapse and many will require an additional course of rituximab. This underpins the importance of understanding the long-term safety profile on repeated treatments. Although rituximab appears to be generally safe, there are concerns about long-term hypogammaglobulinemia, especially in young children. Reliable immunophenotyping and biomarkers are yet to be discovered to predict treatment success, risk of both rare and severe side effects, e.g., persistent hypogammaglobulinemia, and guiding of redosing strategy. In this review, we highlight recent advances in the use of rituximab for childhood nephrotic syndrome and how the therapeutic landscape is evolving.